The crime of aggression under the Rome Statute of the International Criminal Court - McDougall, Carrie, 1978- (Cambridge : Cambridge University Press, 2013)
'This guide to the crime of aggression provisions under the Rome Statute of the International Criminal Court (ICC) offers an exhaustive and sophisticated legal analysis of the crime's definition, as well as the jurisdictional provisions governing the ICC's exercise of jurisdiction over the crime. A range of practical issues likely to arise in prosecutions of the crime of aggression before the ICC are canvassed, as is the issue of the domestic prosecution of the crime. It also offers an insight into the geopolitical significance of the crime of aggression and the activation of the ICC's ability to exercise its jurisdiction over the crime. The author's intimate involvement in the crime's negotiations, combined with extensive scholarly reflection on the criminalisation of inter-State uses of armed force, makes this highly relevant to all academics and practitioners interested in the crime of aggression'--
The crime of aggression under the Rome Statute of the International Criminal Court : an introduction -- Criminalising aggression -- An act of aggression : by any other name -- The elevation of acts of aggression to the state act element of the crime of aggression -- The individual conduct elements of the crime -- The Court's jurisdiction over the crime of aggression -- 2017 and beyond.
Includes bibliographical references (pages 336-373) and index.
Keywords: International criminal court; Rome Statute of the International Criminal Court -- (1998 July 17); Aggression (International law); International crimes